Genre Features of the Novel Epic in Ossetian Literature: Correlation between Ideological and National-Ethnic - I. V. Mamieva (Научный диалог, 2020)
The specific features of epic narration in the Ossetian novel prose (1940-1960) in the context of the all-Russian literary process are considered. The problem solved in the article is actualized in the light of the conceptual differences that emerged in the post-Soviet era in the interpretation of the essence of the concept of “epic novel”, in the attribution of its genre status. The purpose of the article is to specify the typology of the epic chronotope and character system, to identify the issues of the structural completeness of works. A typological method is used with the use of an axiological approach, which allows us to focus both on the spiritual and content aspect of artistic searches and on the pseudo-scale tendencies in the novel-epic practice of the aforementioned decades. The novelty of the work lies in the fact that for the first time, using the example of Ossetian prose, the process of the emergence of a new genre variety in national literatures is investigated. Special attention is paid to the aspects of deactualization of the national-ethnic in the behavioral sphere of characters in favor of sharpening their ideological identity. At the same time, it is shown that in the system of images, in the very poetics of narration, through the ideological sharpening inevitable for time, an orientation toward the foundations of national consciousness, toward the spiritual and historical experience of the people appears. It is concluded that works of an epic type, despite the tangible costs of an ideological and partly aesthetic order, were a new stage in the interpretation of epoch-making events of the past by Ossetian literature in their conjunction with the life of the people, the microcosm of the family and the individual.